Effects of polylactic acid scaffolds with various orientations and diameters on osteogenesis and angiogenesis - Xu, Yun Rong; Tang, Dai Yuan; Xiao, Zhen Ping; Huang, Zai Tian; Zhang, Heng Rui; Tang, Zi Wen; He, Fei (Frontiers in Bioengineering and Biotechnology, 2025)
Researchers in the field of regenerative medicine have consistently focused on the biomimetic design of engineered bone materials on the basis of the microstructure of natural bone tissue. Additionally, the effects of the micromorphological characteristics of these materials on angiogenesis have garnered increasing attention. In vitro, the orientation and diameter of scaffold materials can exert different effects on osteogenesis and vascularisation. However, more comprehensive investigations, including in vivo studies, are required to confirm the results observed in vitro. Accordingly, in the present study, fibre scaffolds with various orientations and diameters were prepared by electrospinning with polylactic acid. The effects of the micromorphological characteristics of these scaffolds with different orientations and diameters on osteogenesis and vascularisation were systematically studied via in vivo experiments. The scaffolds with aligned micromorphological features positively affected osteogenesis and vascularisation, which indicated that such characteristics could be considered crucial factors when designing materials for bone repair.